The Analysis of Digital Learning Platforms Use in EFL Learning - Capriano Ramadhan (Pustaka Digital Indonesia, 2022)
In adaptation of online learning styles, students and teachers faced various challenges at stages. One of them is about the use of learning media. Quizizz and Google Classroom are both the platforms often used in online learning. The purpose of this study is to determine the level of interest and activeness of students while learning using these two medias. Using quantitative methods with the subjects of grade 10 OTKP 2 and 3 of SMK Averus. Based on the results of the analysis of student activity during online learning using Quizizz and Google Classroom, it can be concluded that : (a) From 79 students, 75% participation in learning using Quizizz and 25% did not actively participate, (b) From 79 students, 41% of students participated in learning using Google Classroom and 59% did not actively participate. It can be concluded that despite the similarity in the way the material, assignments and quizzes are given on different platforms show different results. The percentages presented above show concrete results from research on 10th grade students of SMK Averus, that the use of Quizizz as a learning medium is preferred over Google classroom. The attractive appearance and fun atmosphere provided by Quizizz help students live a new learning model (PJJ) during the covid-19 pandemic.